Triterpenoids, steroids and other constituents from Euphorbia kansui and their anti-inflammatory and anti-tumor properties. (December 2022) - Li, Jian-Chun; Li, Shu-Yi; Tang, Jian-Xian; Liu, Dan; Feng, Xiao-Yi; Rao, Kai-Rui; Zhao, Xu-Dong; Li, Hong-Mei; Li, Rong-Tao
Abstract: Six undescribed triterpenoids (euphokanols A−F), two undescribed C21 -steroidal glycosides (euphokanosides A and B), together with fifty-four known compounds were isolated from the roots of Euphorbia kansui . Their structures were demonstrated by extensive spectroscopic data (1D, 2D NMR and HR-ESI-MS), and the absolute configuration of euphokanol A was elucidated based on electronic circular dichroism (ECD) calculation. Among them, euphokanol A was a tetracyclic triterpenoid with a 5, 10-epoxy moiety and concurrent rearrangement of Me-19(10 → 9) and Me-30 (14 → 8), while euphokanols B and C were rare 19(10 → 9) abeo -tirucallane-type triterpenoids with Δ 5(10) double bonds and 7, 8-epoxy moieties. In addition, ten C21 -steroidal glycosides were isolated from Euphorbia plants for the first time. Moreover, cynotophylloside B, caudatin, 5 α, 8 α -epidioxy-22 E -ergosta-6, 22-diene-3 β -ol, 6 β, 7 β -epoxy-3 β, 4 β, 5 β -trihydroxyl-20-deoxyingenol, 13-hydroxyingenol-3-(2, 3- dimethylbutanoate)-13-dodecanoate, ingenol, 3- O -benzoyl-13- O -dodecanoateingenol, 3- O -(2′ E, 4′ Z -decadienoyl)-20- O -acetylingenol, 20- O -acetylingenol and 20- deoxyingenol exhibited significant inhibition on NO production with IC50 values of 9.10, 17.38, 1.71, 0.55, 0.57, 12.22, 0.56, 0.30, 11.21 and 2.98 μM, respectively. Furthermore, wilfoside KIN, cynsaccatol L, kanesulone A, and 3 β, 7 β, 15 β -triacetyloxy-5 α -benzoyloxy-2 α, 8 α -dihydroxyjatropha-6(17), 11 E -diene-9, 14-dione showed cytotoxicity against HepG2 cell line, with IC50 values of 12.55, 12.61, 18.24 and 18.26 μM, respectively. 13-Hydroxyingenol-3-(2, 3-dimethylbutanoate)-13- dodecanoate exhibited anti-proliferation activity on MCF-7 cell line with an IC50 value of 17.12 μM. Specifically, euphol selectively inhibited the growth of human glioma stem cells (GSC-3# and GSC-12#), with IC50 values of 8.89 and 13.00 μM, respectively. Graphical abstract: Image 1 Highlights: Eight undescribed compounds were isolated from Euphorbia kansui. The absolute configuration of euphokanol A was elucidated by ECD calculation. Six compounds showed the most significant inhibitory effects on NO production. Four compounds had obvious cytotoxicity against HepG2 cell line. Three compounds exhibited selective antiproliferative activity against GSCs.